PENGELOLAAN PROGRAM BILINGUAL DALAM PENGEMBANGAN CITRA POSITIF DI MADRASAH IBTIDAIYAH MASLAKUL HUDA PACIRAN LAMONGAN - Ariny Tamamul Minnah (Program Studi Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2022)
The bilingual program is an attempt to introduce two languages to students, especially English which is carried out in the learning process. Educational institutions themselves cannot be separated from the community, because the image of an educational institution is very dependent on the response given by the community to the educational institution as an educational consumer. This study aims to explain: 1) bilingual program planning in building a positive image of madrasas at MI Maslakul Huda Lamongan, 2) implementation of bilingual programs in building a positive image of madrasas at MI Maslakul Huda Lamongan, 3) evaluation and results of bilingual programs in building a positive image madrasa at MI Maslakul Huda Lamongan. The research was conducted using a qualitative approach with the type of case study. The results of this study indicate that: 1) planning a bilingual program at MI Maslakul Huda Lamongan includes: a) recruiting bilingual teachers according to predetermined criteria, b) conducting a survey to adopt the learning system at MI NU Pucang Sidoarjo, c) program teachers bilingual training is included in the training at MI NU Pucang Sidoarjo, d) the bilingual program group teacher always equates perceptions to facilitate the understanding of students from grade one with other classes. 2) the implementation of the bilingual program at MI Maslakul huda includes: a) the implementation of the bilingual program is carried out by the Chair of the Foundation, the Principal and the person in charge of the bilingual program, b) the implementation of daily activities such as dhuha prayers, UMMI programs and other schedules, c) facilities that can support learning activities, d) there is an agenda book for monitoring students. 3) evaluation and results of the bilingual program in developing a positive image at MI Maslakul Huda Lamongan include: a) evaluation is carried out every 6 months and is conditional, b) evaluation is carried out by the head of the foundation, school principal, bilingual program coordinator and the teachers concerned, c) the evaluation process is carried out by holding a meeting, d) one of the parents said that the public's view of MI Maslakul Huda is very good so that it can create a positive image.